Halitose na geriatria: diagnóstico, causas e prevalência - Guiotti, Aimée Maria [UNESP]; Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP]; Turcio, Karina Helga Leal [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Gonçalves, Heloisa Helena Silva Bolzan; Fantasia, Ricardo (My University, 2014)
Halitosis is the unpleasant odor of exhaust air through the mouth and lungs. There are over 50 causes, and approximately 90% of cases, is of oral origin. May have physiological origin (stress, breath of morning, fasting, and inappropriate diets), local reasons (bad oral hygiene, bacterial plaque retained on the tongue and/or tonsils, lower production of saliva, gum disease) or systemic reasons (diabetes, kidney or liver problems, constipation, etc.). In the Third Age, this problem tends to increase significantly. Thus, the aim of this study was to detect the presence of halitosis in the geriatric group attended in the dental clinic of UNIRP, identifying their incidence and principal causes. The sample consisted of 48 volunteer patients aged 60 years or older and included more than 90% of patients treated in this age group. It was performed a anamnesis and physical examination. The intra-oral halitosis was detected using a breath meter (halimeter). In the group studied, approximately 54.16% had halitosis, 84.61% of these were users of the prosthesis. The tongue coating was present in 80.76% of individuals with halitosis. After brushing the tongue, 88.46% of patients with halitosis have had the initial index oral malodor decreased. Based on the results of this study it was concluded that factors as dental prostheses and tongue coating are critical factors in causing halitosis.

Halitose é o odor desagradável do ar expelido pela cavidade oral, narinas ou faringe. Este odor origina-se principalmente pela presença de compostos sulfurados voláteis produzidos por bactérias presentes na cavidade oral. Pode ter origem fisiológica (estresse, hálito da manhã, jejum prolongado, dietas inadequadas); razões locais (má-higiene bucal, biofilme retido na língua e/ou amígdalas, baixa produção de saliva, gengivites e periodontites) ou mesmo razões sistêmicas (diabetes, problemas renais ou hepáticos, dentre outros). Na Terceira Idade, este problema tende a aumentar significativamente, devido a diversos fatores. Dessa forma, o objetivo deste estudo foi diagnosticar a presença de halitose no grupo geriátrico atendido na clínica odontológica da UNIRP, identificando sua incidência e principais causas. A amostra constituiu-se de 48 pacientes voluntários com 60 anos ou mais e abrangeu mais de 90% dos pacientes nessa faixa etária ali atendidos. Foram realizados uma anamnese e exame físico intra-oral e a halitose foi detectada utilizando um halímetro portátil. No grupo pesquisado, aproximadamente 54,16% apresentou halitose, destes 84,61% eram usuários de prótese. A saburra lingual esteve presente em 80,76% dos indivíduos com halitose. Após a escovação lingual, 88,46% dos portadores de halitose tiveram o índice inicialmente aferido pelo halímetro diminuído. Com base nos resultados deste estudo, concluiu-se que fatores como uso de próteses dentárias e presença de saburra lingual são determinantes etiológicos no surgimento da halitose.
Oral malodor in geriatric population: diagnosis, causes and prevalence
Keywords: Geriatric Dentistry; Halitosis; Oral hygiene; Dental prosthesis; Odontologia geriátrica; Halitose; Higiene bucal; Prótese dentária